Exposición a alérgenos y su influencia en el asma bronquial en pacientes menores de 5 años que asisten al Instituto Ecuatoriano De Seguridad Social Babahoyo primer semestre 2018. - Carbo Smith, Kerly Tatiana (2018)
Allergenic exposures are one of the most influential consequences for children suffering from bronchial asthma since environmental pollution, smoke from certain psychotropic substances, pollen and animals are the factors that most affect our children. Through this project, which was carried out in the IESS Babahoyo hospital, an attempt was made to solve the problem by which children under 5 years of age with bronchial asthma problems arrive in Babahoyo canton in the province of Los Ríos during the 2018 semester. A field study, exploratory and descriptive, through the use of the deductive, analytical and synthetic method, with a qualitative-quantitative approach. The universe of study was 100 children under 5 years of age who entered the outpatient area of the IESS Hospital of the Babahoyo Canton of Los Ríos Province during the first semester of 2018 and the study sample was 100% of people. The purpose is to encourage parents of children who come to the IESS Babahoyo hospital, to attend the talks that were projected by the health staff giving them to know what are the factors that influence and how to prevent bronchial asthma in young children 5 years old.